Prevalence and Characterization of Diarrheagenic Escherichia coli Isolated from Adults and Children in Mangalore, India - Shetty, Veena A; Kumar, Sanath H; Shetty, Avinash K; Karunasagar, Iddya; Karunasagar, Indrani (Journal of Laboratory Physicians, 2012)
Background: Diarrheal diseases are a major cause of morbidity and mortality in resource-limited countries. Among the bacterial pathogens, diarrheagenic E. coli (DEC) are most frequently implicated in cases of epidemic and endemic diarrhea worldwide. The objective of this study was to determine the prevalence of DEC in stool specimens from patients with acute diarrhea using polymerase chain reaction (PCR).Materials and Methods:Escherichia coli stool samples were collected from 115 hospitalized children and adults with acute diarrhea in Mangalore, a coastal city, in southern India. PCR amplification of eae, bfp, stx, ehx genes were used for detection of enteropathogenic (EPEC) and shigatoxigenic E. coli (STEC), lt and st genes were used for enterotoxigenic E. coli (ETEC) and astA gene for enteroaggregative E. coli (EAEC).Results: During the 24 month study period, of the 115 stool samples, DEC type was detected in 20 (17.4%) using the PCR method. The most prevalent DEC was atypical EPEC accounting for 12 (10.4%) cases followed by 4 cases of EAEC (3.4%) and 4 of STEC (3.4%). No ETEC strains were isolated from any of the examined stool samples.Conclusion: This study suggests that the atypical EPEC are the newly emerging group among DEC stains in Southern India. Further studies are needed to evaluate the epidemiology and virulence properties of atypical EPEC strains.
Keywords: Atypical; diarrhea; enteropathogenic; Escherichia coli; polymerase chain reaction